2002
DOI: 10.1177/230949900201000110
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Chronic Osteomyelitis with a Biodegradable Antibiotic-Impregnated Implant

Abstract: The use of local antibiotics from a biodegradable implant for chronic osteomyelitis is an attractive alternative. The implant delivers high tissue levels, obliterates dead space, aids bone repair and does not need to be removed. The purpose of this paper is to review our early clinical experience with custom-made calcium sulfate (Osteoset bone void filler) antibioticimpregnated implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
140
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(147 citation statements)
references
References 15 publications
4
140
0
3
Order By: Relevance
“…Similar research on the conventional, uncrushed pellets, which are designed to elute antibiotic over a period of 28 days and used clinically to eradicate an existing infection, release concentrations of roughly 1,000 mg/ml/g over the first 24 h and 10 mg/ml/g over the next 24 h, sufficient levels to prevent antibiotic growth for weeks. 9,14,18,28,29 With such immediate antibiotic elution from conventional flakes, the in vitro work of this study does not suggest that a large difference in initial antibiotic concentration would occur between flakes and an injection. 7 Comparing the characteristics for the FAST pellet and the conventional flakes by Yarboro, we found that the FAST pellet dissolved more quickly and eluted antibiotic at a more sustained rate.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Similar research on the conventional, uncrushed pellets, which are designed to elute antibiotic over a period of 28 days and used clinically to eradicate an existing infection, release concentrations of roughly 1,000 mg/ml/g over the first 24 h and 10 mg/ml/g over the next 24 h, sufficient levels to prevent antibiotic growth for weeks. 9,14,18,28,29 With such immediate antibiotic elution from conventional flakes, the in vitro work of this study does not suggest that a large difference in initial antibiotic concentration would occur between flakes and an injection. 7 Comparing the characteristics for the FAST pellet and the conventional flakes by Yarboro, we found that the FAST pellet dissolved more quickly and eluted antibiotic at a more sustained rate.…”
Section: Discussionmentioning
confidence: 94%
“…2,5,[7][8][9][13][14][15][16]19 We evaluated the dissolution, elution, and biological activity of fastdegrading drug delivery vehicles made from cellulose binder and calcium sulfate dihydrate and from conventional calcium sulfate alpha-hemihydrate crushed into flakes. While this study used the Yarboro-type crushed conventional cast antibiotic-loaded calcium sulfate pellet as a comparison, the crushing/compressing of commercially available calcium sulfate pellets with tobramycin is not recommended by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 Moreover, the size of the granules is also adequate to perform in vivo studies using an osteomyelitis rat model. 25 SEM images revealed the presence of interconnective macroporosity, which is desirable for bone tissue regeneration, as interconnectivity allows cell migration, neovascularization, and transport of nutrients and proteins.…”
Section: Discussionmentioning
confidence: 99%